„Nasza Francja”. Julian Klaczko o wartościach, wolności wyboru i lojalności - Iwona Węgrzyn (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria)
The presented text attempts to characterize the unique relationship between Julian Klaczko and France. By recalling the content of a speech delivered by the writer in 1870 at the Galician Parliament in Lviv, the forgotten 'Travel Notes' from 1871, and the 'Florentine Evenings' of autumn 1872, I aim to reconstruct the writer’s emotionally charged response to the events surrounding the Franco-Prussian War, the fall of the Second Empire, and the outbreak of the Paris Commune. This narrative proves to be not only a record of individual experience but also a generational one – a testament to the disintegration of the myth crafted by Polish Romantics, who found refuge in France after the failure of the January Uprising.